Pembuatan Almond Crispy Tepung Mocaf Dengan Taburan Biji Ketapang - Ira Handayani; Wikan Wicaksono (Garina, 2023)
Almond crispy is one of the flat-shaped pastries and crunchy texture that is quite popular in Indonesia. As an effort to innovate the almond crispy almond crispy ingredients are diversified with mocaf flour and given a sprinkling of ketapang seeds. The purpose of this study is 1) to determine the public's acceptance of almond flour crispy Mocaf with Ketapang seed sprinkles; 2) to determine the composition of materials used in the manufacture of almond flour crispy ketapang seed sprinkles mocaf the most preferred community. The research methods used are library methods, experiments, documentation, questionnaires and sensory tests. The results showed that almond crispy mocaf flour with a sprinkling of ketapang seeds using 100% mocaf flour is the most preferred product. The composition of the ingredients used in the manufacture of almond crispy mocaf flour with Ketapang seed sprinkles consists of 100 g of mocaf flour, 80 g margarine, 80 g refined sugar, 30 g egg white, 20 g cornstarch, 20 g butter, 10 g Ketapang seeds, and 1 g salt.